Network Analysis of Pathogenesis Markers in Murine Chagas Disease Under Antimicrobial Treatment - Nayra Dias; Marina Dias; Andressa Ribeiro; Nélio Gomes; Aline Moraes; Moisés Wesley; Carlito Gonzaga; Doralina do Amaral Rabello Ramos; Shélida Braz; Bruno Dallago; Juliana Lott de Carvalho; Luciana Hagström; et al. (Microorganisms)
Chagas disease (CD), a disease affecting millions globally, remains shrouded in scientific uncertainty, particularly regarding the role of the intestinal microbiota in disease progression. This study investigates the effects of antibiotic-induced microbiota depletion on parasite burden, immune responses, and clinical outcomes in BALB/c mice infected with either the Trypanosoma cruzi Colombiana or CL Brener strains. Mice were treated with a broad-spectrum antibiotic cocktail before infection, and parasite burden was quantified via qPCR at 30 and 100 days post-infection (dpi). Immune responses were analyzed using flow cytometry and ELISA, while histopathology was conducted on cardiac and intestinal tissues. Antibiotic treatment uncovered strain-specific correlations, with Colombiana infections affecting Bifidobacterium populations and CL Brener infections linked to Lactobacillus. Microbiota depletion initially reduced parasite burden in the heart and intestine, but an increase was observed in the chronic phase, except in the CL Brener-infected gut, where an early burden spike was followed by a decline. Antibiotic-induced bacterial shifts, such as reductions in Bacteroides and Bifidobacterium, promoted a more pro-inflammatory immune profile. These findings highlight the importance of microbiota and strain-specific factors in CD and suggest further research into microbiota manipulation as a potential therapeutic strategy.